1981
DOI: 10.1128/iai.32.1.38-41.1981
|View full text |Cite
|
Sign up to set email alerts
|

Effects of surgery on neutrophil granulocyte function

Abstract: The high incidence of postoperative infections raises the possibility of a reduced defense to infection during this period. For this reason, neutrophil function and enzyme activity were investigated after surgical trauma. The microbicidal ability of neutrophils was markedly impaired within 2 h of elective abdominal hysterectomy, but phagocytosis was unaffected. Loss of microbicidal activity was associated with loss of the lysosomal enzyme myeloperoxidase. It is suggested that these changes are due to activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
1

Year Published

1983
1983
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(14 citation statements)
references
References 18 publications
(22 reference statements)
3
10
1
Order By: Relevance
“…More recent reports have revealed evidence of an activation rather than a depression of neutrophils in the early postoperative period ( 1 1, 27). As for non-infected patients, our results confirm these observations and are in good agreement with studies showing unchanged or even enhanced PMN functions following non-cardiovascular major surgery (28)(29)(30)(31). It is suggested that these changes are due to an in vivo activation of circulating neutrophils (28).…”
Section: Discussionsupporting
confidence: 92%
“…More recent reports have revealed evidence of an activation rather than a depression of neutrophils in the early postoperative period ( 1 1, 27). As for non-infected patients, our results confirm these observations and are in good agreement with studies showing unchanged or even enhanced PMN functions following non-cardiovascular major surgery (28)(29)(30)(31). It is suggested that these changes are due to an in vivo activation of circulating neutrophils (28).…”
Section: Discussionsupporting
confidence: 92%
“…Such changes are associated with the development of defects in neutrophil function and may predispose to secondary infection (Davies et al, 1980). Similar defects in neutrophil function have been observed in patients undergoing major surgery (Bowers et al, 1977;El-Maallem & Fletcher, 1981). The present study was undertaken to determine whether major surgery was also accompanied by changes in levels of neutrophil granule proteins.…”
supporting
confidence: 68%
“…6 Surgery did not change the phagocytic capacity of PMNs from patients with AM in the presence of normal plasma, supporting the results of others that the intrinsic phagocytic capacity of PMNs is not affected by surgery. [7][8][9] However, in the presence of autologous plasma, PMN phagocytosis of patients with AM decreased by 30% within 2 hours after surgery. This decrease in phagocytic capacity of PMNs correlated with the postoperative decrease in plasma C3 and IgG levels, two opsonins essential for optimal ingestion of bacteria, 7,10,11 suggesting that the decreased phagocytosis after abdominal surgery was caused by a decrease of circulating plasma opsonins, as found by others.…”
Section: Discussionmentioning
confidence: 99%